2019
DOI: 10.3390/atmos10090554
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Monitoring of Methane in Beijing Using a Mobile Observatory

Abstract: Cities have multiple fugitive emission sources of methane (CH4) and policies adopted by China on replacing coal with natural gas in recent years can cause fine spatial heterogeneities at the range of kilometers within a city and also contribute to the CH4 inventory. In this study, a mobile observatory was used to monitor the real-time CH4 concentrations at fine spatial and temporal resolutions in Beijing, the most important pilot city of energy transition. Results showed that: several point sources, such as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The intake was linked/connected through a 2 m pipe with a particulate matter filter to Picarro (Figure 3A and 3B). The instruments characteristics and precision have been described by Sun et al(Sun et al, 2019). The CO 2 concentrations were collected every 2 seconds and then averaged into 1-minute intervals.…”
Section: On-road Co 2 Concentration Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The intake was linked/connected through a 2 m pipe with a particulate matter filter to Picarro (Figure 3A and 3B). The instruments characteristics and precision have been described by Sun et al(Sun et al, 2019). The CO 2 concentrations were collected every 2 seconds and then averaged into 1-minute intervals.…”
Section: On-road Co 2 Concentration Datamentioning
confidence: 99%
“…The global positioning system (GPS) data during BC and DC were collected by a GPS receiver (BS-70DU) (Sun et al, 2019).…”
mentioning
confidence: 99%
“…In the last decade, the deployment of mobile urban pollution monitoring systems using different platforms (e.g., trains, bikes, other vehicles) have been demonstrated in many cities across the world, such as Brisbane, Australia [22], Ontario, Canada [23], Oakland, California [24], Beijing, China [25], Seoul, Korea [26], and Hong Kong [27]. A recent effort to outfit Google street cars across several US cities has also been successful in mapping fine-scale urban pollution gradients [24,25,28,29]. The importance of combining these mobile platforms with fixed-site platforms to derive highly resolved spatial pollution maps and related pollutant exposure metrics is a very active area of research [30][31][32].…”
Section: Overview Of Recent Mobile Urban Air Quality Studiesmentioning
confidence: 99%
“…CH 4 is radiatively stronger than CO 2 on a mass basis and it is reported that the current global warming potential of CH 4 is 25 times higher than that of CO 2 over a 100 year period [7]. Most previous studies on composting and vermicomposting have focused on the feasibility of different organic wastes and the factors affecting the growth and reproduction rate of earthworms as well as the quality of the compost and vermicompost [8]. However, little is known about the emissions of CO 2 and CH 4 during the composting and vermicomposting of sewage sludge.…”
Section: Introductionmentioning
confidence: 99%